Pengaruh Current Ratio, Cash Ratio, dan Total Assets Turnover terhadap Net Profit Margin pada Industri Makanan dan Minuman Periode 2013-2017 - Puja Widiani (Science of Management and Students Research Journal (SMS), 2019)
This research aims to analyze how the effect of Current Ratio, Cash Ratio, and Total Assets Turnover, on Net Profit Margin in the food and beverage industry. Furthermore, also to find out which Variables of Current Ratio, Cash Ratio, and Total Assets Turnover, which predominantly affect Net Profit Margin in the Food and Beverage Industry. This research uses quantitative descriptive analysis method and qualitative descriptive analysis, namely data expressed in the form of statements / sentences and data expressed in the form of numbers. The analytical tool in this study uses the classical assumption test, with proof of normality test, multiconearity test, autocorrelation test, and and heteroscedacity test, also using multiple linear regression, F test, t test. The results of the study show that simultaneously the variables Current Ratio, Cash Ratio, and Total Assets Turnover have a significant effect on Net Profit Margin. Where the value of Fcount is 32,089> Ftable of 2.98 and prog. Sig 0,000 <alpha 0.05. The results of the t-test show that partially the current ratio has a significant effect on Net Profit Margin, where t count> t table (4,099> 2.055) with a significant 0.000 <0.025, while the two other variables namely Cash Ratio and Total Assets Turnover do not significantly influence Net Profit Margin . And the coefficient And the coefficient of determination is 78,7%, while the remaining 21.3% is influenced by other studies. Keywords: Current Ratio, Cash Ratio, Total Assets Turnover, and Net Profit Margin